Saving Behavior of Clove Farmer Households in the Form of Commodities (Case Study in Negeri Ullath Maluku Indonesia) - Jeanee Nikijuluw (Jurnal Multidisiplin Madani, 2023)
This interdisciplinary study aims to understand the saving behavior of farmer households in the form of commodities done in a qualitative manner. The results of exploration, identification and analysis found that (i) economic, psychological and socio-cultural factors influenced the household behavior, and they were interconnected with one another; (ii) there was a maximum utility of households when they were being tolerant of risks supported by self-efficacy; (iii) the clove-saving behavior was related to prestige and social status; and (iv) saving decisions were dominated by psychological factors